1998
DOI: 10.1002/etc.5620170722
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of in situ exposure of fish to secondary treated bleached‐kraft mill effluent using a laboratory simulation

Abstract: Abstract-To corroborate the responses in whitefish (Coregonus lavaretus L.) exposed to elemental chlorine free (ECF) bleachedkraft pulp mill effluent (BKME) in situ, a 30-d laboratory exposure was carried out at concentrations simulating the field conditions. The flow-through exposures were conducted at four secondary (activated sludge) treated effluent (STE) concentrations: 1.3, 2.3, 3.5, and 7%. To evaluate the role of the secondary treatment, fish were also exposed to one concentration (3.5%) of pretreated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, after the industry adopted elemental chlorine-free and totally chlorine-free bleaching processes and installed secondary effluent treatment, reproductive effects in wild and laboratory fish continued to be reported [5,6]. Fish exposed to BKPME in the field and in the laboratory had reduced gonad size, decreased fecundity, altered expression of secondary sex characteristics, increased age at reproductive maturation, and depressed plasma and gonadal production of reproductive steroid hormones [14][15][16][17]19,20,35]. Exposure to environmentally relevant concentrations of BKPME resulted in significant depressions in plasma testosterone levels in both sexes of perch [13], white sucker [14,35], and juvenile whitefish [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, after the industry adopted elemental chlorine-free and totally chlorine-free bleaching processes and installed secondary effluent treatment, reproductive effects in wild and laboratory fish continued to be reported [5,6]. Fish exposed to BKPME in the field and in the laboratory had reduced gonad size, decreased fecundity, altered expression of secondary sex characteristics, increased age at reproductive maturation, and depressed plasma and gonadal production of reproductive steroid hormones [14][15][16][17]19,20,35]. Exposure to environmentally relevant concentrations of BKPME resulted in significant depressions in plasma testosterone levels in both sexes of perch [13], white sucker [14,35], and juvenile whitefish [17].…”
Section: Discussionmentioning
confidence: 99%
“…Fish exposed to BKPME in the field and in the laboratory had reduced gonad size, decreased fecundity, altered expression of secondary sex characteristics, increased age at reproductive maturation, and depressed plasma and gonadal production of reproductive steroid hormones [14][15][16][17]19,20,35]. Exposure to environmentally relevant concentrations of BKPME resulted in significant depressions in plasma testosterone levels in both sexes of perch [13], white sucker [14,35], and juvenile whitefish [17]. Testosterone is the dominant androgenic hormone in fish and serves as a precursor for other sex steroids such as 11-ketotestosterone in males and 17␤-estradiol in females; the former functions in expression of secondary sexual characteristics and the latter in the synthesis of yolk proteins for developing follicles [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were fed ad libitum with Trout Grower 3 PT (Martin Mills Profishnet Feed, Tavistock, ON, Canada) three times a week until 3 d before the start of exposures [12]. For ip injections, trout of similar size were obtained from the Laukaa Fish Culture Research Station (Central Finland) and held under similar conditions in dechlorinated City of Jyväskylä water [15].…”
Section: Introductionmentioning
confidence: 99%
“…The applied experimental regimens and the areal distribution, based on previous "eld investigations considering the fate of BKME-derived substances (Soimasuo et al, 1998b;LeppaK nen et al, 1999), allowed comparisons between studies of two consecutive years. Previous laboratory studies had found that the BKMEs involved in the present study a!ect, without changeable environmental factors, the physiology of white"sh in several ways (Soimasuo et al, 1998a). These include modi"ed responses of liver and red blood cells to acute handling disturbance (Lappivaara, 2000).…”
Section: Introductionmentioning
confidence: 98%